A Pragmatic Study of Deixis in the Lyrics of the Worship Song 'As the Deer' by Martin Nystrom - Joi Ravido Manurung; Bernieke Anggita Ristia Damanik (Journal of Human Interaction and Social Studies, 2026)
This study investigates how deictic expressions function within the written lyrics of Martin Nystrom's 1984 contemporary Christian hymn titled As the Deer. Utilizing a nonempirical qualitative content analysis anchored in classical pragmatic theories, the investigation isolates person, spatial, and temporal reference systems to decode how meaning is derived from the communicative event. The findings reveal a highly specialized structural asymmetry within the text. Interpersonal indexical markers occur with extreme frequency, establishing a direct and intimate dialogic connection between the worshipper and the divine addressee. Conversely, physical spatial indices and historical chronological markers are completely neutralized, creating a spatial vacuum and a chronological suspension. This strategic omission decouples the discourse from specific geopolitical or historical boundaries, generating a state of eternal immediacy that remains universally adaptable across diverse communities. Ultimately, the research demonstrates that the text transforms individual devotion into an ongoing psychological reality, confirming the utility of pragmatic frameworks for decoding sacred discourse.